Histopathological Alterations and Bioaccumulation in Mussel Perna viridis Exposed to Sub-lethal Concentrations of Cadmium - Sreejamole, K L (Fishery Technology, 2025)
Bioaccumulation of heavy metal, cadmium and its histolopathological effects on gills and hepatopancreas in the Indian green mussel Perna viridis were assessed on the basis of 96 h LC50. The mussels were exposed to sublethal concentrations of cadmium (0.01, 0.025, 0.05, 0.1, 0.2 and 0.4 ppm) for 21 days. The whole tissue of mussels was dried at 65oC for 72 h and was subjected to acid digestion and analysed for cadmium content using AAS. A dose and time dependent increase in accumulation of cadmium was observed for 15 and 21 days of exposure. Higher concentration (0.4 ppm) showed an abrupt increase in cadmium content compared to other lower concentrations. Histopathological analysis showed significant alterations in the structure of gills and hepatopancreas on cadmium exposure for 21 days. Loss of cilia, disruption of epithelial cells and hyperplasia were observed. Hepatopancreas showed bulging and enlargement of digestive tubule and disruption of collagenous layer.